Women Entrepreneurs and the Pricing Dilemma - Koshy, Moli P.; Joseph, Mary (Indian Journal of Marketing, 2011)
What price is to be charged for a product or a service is a question that haunts an entrepreneur at a crucial stage of the marketing process. Small scale entrepreneurs tend to take mainly cost of production as the basis for setting the price. Women entrepreneurs often leave it to the men of the family, even though they strive to bring out the product in the market. Most of the time, these small-scale entrepreneurs tend to overlook the hidden costs and the need for development. Pricing objectives of most of the women entrepreneurs tend to be stuck at market penetration or meeting the competition, thereby maintaining their organization with the sustenance objective. Majority of the women entrepreneurs do not change their pricing method to gain the optimum benefits during the course of time in their business. And when they change the price, it is following the herd rather than leading or initiating the price changes. This paper outlines the pricing practices and hurdles of women entrepreneurs in pricing their products during various stages in the course of their business in Kerala.